Effectiveness of hyaluronic acid on wound healing post periodontal surgery: Efektivitas hyaluronic acid pada penyembuhan luka pasca bedah periodontal - Winawan, Irma; Thahir, Hasanuddin; Setiawati, Dian (Makassar Dental Journal PDGI Makassar, 2024)
The management of periodontal cases is orientated towards the repair of decayed structures and elimination of inflammation. In severe conditions, invasive procedures such as periodontal surgery are indicated to achieve maximum results. Tissue regenera-tion becomes the next focus after surgical procedures are performed. Hyaluronic acid is one of the potential materials to be used post-surgical therapy given its regenerative effect on wound tissue. This study evaluates the effectiveness of HA application on periodontal post-surgical wounds. The literature search was conducted using Science Direct, Plos One and Pubmed, then the re-view and synthesis process was carried out using PRISMA. 1638 articles were found and 6 articles were included in the study. It was concluded that the use of hyaluronic acid is effective in accelerating wound healing and pain reduction after periodontal surgery.